A retrospective analysis of iv ketamine outcome on hospitalizations in an unselected psychiatric sample - Sandström, Karl (Cambridge University Press (CUP), 2025)
Objective: This study aims to explore the outcome with iv ketamine treatment in a real-world clinical setting, primarily measured as posttreatment days hospitalized.
Methods: The psychiatric medical records of 46 patients having received iv ketamine on a psychiatric treatment indication between 2015-2018 were retrospectively examined. Analysis comparing the number and duration of hospital admissions before and after ketamine treatment as well as logistic regression analysis to investigate clinical predictors of effectiveness, were performed. To assess patients' severity of depressed symptoms records were screened for MADRS-S scores.
Results: No significant difference between pre- and posttreatment hospital days (p=0.170), or number of hospitalizations (p=0.740) were found. The response rate was 31% and remission rate 21%. None of the predictors showed statistical significance in the logistic model.
Conclusion: Iv ketamine treatment showed effectiveness in reducing depressive symptoms even with complex patients in a real-world clinical setting. However, this did not translate to a reduction in hospitalization. Highlighting the multifaceted challenges posed when implementing iv ketamine treatment in clinical practice.